Students’ Attitude on Languages They Acquired, Learned, and Use: A Case Study of Double Major Students - Magpika - Handayani; Aries Utomo (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2026)
People's movement and the world's quick changes have an impact on language use nowadays. This condition makes it difficult for people to maintain the language they have learned, such as their first and second language, in order to continue interacting with their community, or to learn a new language in order to be able to communicate with others for specific purposes, such as future preparation and environment adaptation. This study examines the views of double major students toward the languages they have studied, acquired, and used in an attempt to comprehend how students view globalization. It describes how the students view English as the language they have learnt, and Khek, Tio Ciu, and Bahasa Indonesia as the languages they have learned and used. By elucidating the preliminary analysis and focusing on the data to portray students' attitudes on the language they learned, acquired, and utilized, the data were investigated inductively. The findings indicate that students pursuing a double major at Politeknik Tonggak Equator have a positive attitude toward Khek or Tio Ciu and Bahasa Indonesia as the languages they have learned and use. Additionally, they have a similar attitude toward English as the language they have learned because they value and receive it emotionally. Since each of their three languages has a specific function in their communication, they demonstrate their loyalty, pride, and awareness of the usage of their first, second, and third languages.Keywords: Students’ attitude, Language Acquired, Learned and Use, Case Study